Purchase Intention towards Life Insurance Policies among Generation Y - Tay, Jing Ren (2014)
In the recent years, the life insurance industry has experienced a rapid growth in Malaysia. Yet, the penetration rate of Life insurance remains low, as compared with the other Asian countries. Obviously, there is large room for improvement in the life insurance sectors in Malaysia. Besides that, the Generation Y has become the large population of the total generation population in Malaysian and they have a high purchasing power towards the goods and services. Thus, this research aims to investigate the factors that influence purchase intention toward life insurance policies among the Generation Y in Malaysia through the framework of Theory of Planned Behavior model (TPB). The framework was developed and this research was conducted through quantitative approach. The 384 questionnaires were distributed of the Generation Y who ages between 20-37 years old in Malaysia for the analysis purpose. The data collected was analyzed by using the SPSS software and the results show that the six independent variables, product knowledge, perceived benefit, perceived risk, attitude, social influence and self-efficacy have a relationship with the purchase intention toward life insurance policies among the Generation Y in Malaysia. The results of this research are believed to be able to provide useful insights and important implication to financial institutions, academician and the society as a whole in yielding higher penetration rate of life insurance policy. Several implications and recommendations are being discussed in Chapter 5